IMPLEMENTASI MODERASI BERAGAMA MELALUI PENDIDIKAN AGAMA ISLAM DI SEKOLAH DEMI MENANGGULANGI SIKAP INTOLERANSI - Fatkhur (Al-Iqro', 2024)
Religious moderation has principles that need to be implemented in educational institutions such as schools through Islamic religious education learning, this is because there is still an attitude of intolerance in educational institutions that continues to be suppressed by the implementation of religious moderation. this research uses qualitative methods and includes library studies. The results found in this study that the implementation of religious moderation through Islamic religious education is important to eliminate intolerant attitudes with the step of the teacher's approach as an educator providing inclusive learning and providing an attitude of the importance of mutual respect despite different beliefs.